PENGEMBANGAN MEDIA PEMBELAJARAN MENTARI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS KELAS IV SEKOLAH DASAR - Putri, Anggita Shahida; Riswari, Lovika Ardana; Fardani, Much Arsyad (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to develop MENTARI learning media (E-Module in the Form of Flipbook Maker Flat Buildings Based on Ethno-Mathematics) for the Mathematical problem-solving abilities of grade IV SD 1 Mejobo. Flipbook maker media can present learning materials in the form of words, sentences, pictures, and animations which can be equipped with colors. This study applied a research and development approach. The data collection instruments were interview, observation, documentation, and test methods, with quantitative data analysis techniques. Quantitative data analysis through validation data analysis, normality tests, and N Gain Tests. The normality test of pretest and posttest data is normally distributed, because the pretest significance is 0.209>0.05 and the posttest significance is 0.917>0.05. In this test, the N-Gain results obtained were an average increase of 0.69 with the "moderate" category. The conclusions of this study are: (1) the average score of the material validity test is 93% also with the "very feasible" feasibility category; (2) Based on the questionnaire responses from 15 fourth grade students, the average score was 92% with the category "very appropriate"; (3) the average N-Gain percentage was 69.20% with the effectiveness interpretation criteria of "quite effective".